Preoperative contrast-enhanced ultrasound (CEUS) of long bone nonunions reliably predicts microbiology of tissue culture samples but not of implant-sonication - Dapunt, Ulrike A.; Zhao, Yina; Schmidmaier, Gerhard; Fischer, Christian (Orthopaedics & traumatology, 2022)
Introduction - Bacterial infection in the context of fracture repair remains a severe complication in trauma surgery and may result in long bone nonunion. Since treatment options for aseptic and infected nonunions vary greatly, diagnostic methods should ideally differentiate between these two entities as accurately as possible. Recently, contrast-enhanced ultrasound (CEUS) has been introduced as a preoperative imaging technique to evaluate hypervascularity at the fracture site as sign of bacterial infection. - Hypothesis - Preoperative CEUS predicts results of microbiological evaluation obtained either by culture of tissue samples or by analyzing the sonication fluid following removal and sonication of the implant. - Patients and methods - Over the course of 6 months, 26 patients with long bone nonunions were included in this study. Patients’ clinical data were evaluated. Tissue samples were collected intraoperatively and examined by standard microbiological techniques. The sonication method was applied to removed implants. Additionally, 1-3 days before surgery, CEUS was performed to determine hypervascularity at the nonunion site as a possible parameter for infection. - Results - Culture of tissue samples indicated infection in 50% of cases and implant sonication in 57.7% of cases. However, there was merely a fair agreement (κ=0.231) between these two diagnostic methods. CEUS predicted results of tissue culture reliably (sensitivity 92.3% and specificity 100%), whereas implant sonication showed no significant correlations with results from CEUS. Hypertrophic and atrophic nonunions were evaluated separately to determine possible differences in vascularity. We found that contrast peak enhancement of CEUS was similar in atrophic and hypertrophic nonunions with positive culture of tissue samples. Both differed significantly from culture negative cases (p=0.0016 and 0.0062). Results of implant-sonication positive or negative cases in atrophic and hypertrophic nonunions, however, were less clear and could be misleading. - Discussion - We were able to confirm CEUS as a valuable preoperative diagnostic tool that reliably predicts microbiology of tissue culture samples, but not of implant sonication. - Level of evidence - I; diagnostic study.
Available online 18 February 2021
Gesehen am 20.10.2022